The Impact of service innovation on tourist satisfaction: Evidence from the Malaysian tourism industry - Cheng, Boon Liat * (Global Academy of Training & Research (GATR) Enterprise, 2014)
Objective – This study proposed a model to test the impacts of the four dimensions of service innovation (i.e., process innovation, organisational innovation, marketing innovation and product innovation) on tourist satisfaction in the Malaysian tourism. Methodology/Technique – Measurement items for the dimensions of service innovation were developed through focus group interviews. A convenience sampling approach was adopted with the distribution of 400 questionnaires among local and foreign tourists. Statistical tolls in the Statistical Package for the Social Sciences (SPSS) were adopted to analyse the reliability of items and the hypothesised relationships in the proposed research model. Findings – The findings reveal that the respective dimensions of service innovation are significantly related to tourist satisfaction. These findings contribute to the services marketing body of knowledge by providing insight on the impact of service innovation on tourist satisfaction. Novelty – Limited studies have been done to examine the impact of service innovation dimensions on tourist satisfaction. The findings of this study contribute to the services marketing body of knowledge by providing insight on the impact of service innovation on tourist satisfaction. At the same time to address the practical implications by recommending relevant and effective service innovation strategies for the tourism industry in Malaysia. This knowledge is useful for benchmarking better service innovation practices among the industry practitioners.